LPI Security Essentials Study Guide Exam 020-100 - Clinton, David (IT specialist) (John Wiley & Sons, Incorporated, 2023)
Prepare smarter and faster for the LPI Security Essentials exam In LPI Security Essentials Study Guide: Exam 020-100, veteran Linux server administrator David Clinton delivers an expert tutorial on the major security threats facing computers, networks, connected devices, and IT services, both on-premise and in the cloud. You'll discover common and effective ways to prevent, mitigate, and respond to security attacks, and validate your ability to use encryption to secure data transferred through a network. This book is designed to prepare you for the LPI Security Essentials certification offered by the global standard and career support organization for open-source professionals. Whether you're preparing for this foundational exam as a steppingstone to the more advanced Security+ certification or as an end in itself, you'll advance your knowledge of security concepts, encryption, node, device, and storage security, network and service security, and identity and privacy concepts. You'll get: Techniques and tools you can use immediately in a new role as an IT security professional Key strategies for digital self-defense, including securing your own devices and making use of IT services Complimentary access to Sybex's superior online interactive learning environment and test bank, complete with chapter tests, a practice exam, electronic flashcards, and a glossary of key terms Perfect for anyone seeking to take the LPI Security Essentials certification exam, LPI Security Essentials Study Guide, Exam 020-100 is a must-have resource for people looking to hit the ground running in a new career focused on information security.